Comparison of low-temperature fracture and strength properties of asphalt mixture obtained from IDT and SCB under different testing configurations. Issue 3 (3rd April 2018) - Falchetto, Augusto Cannone; Moon, Ki Hoon; Wang, Di; Riccardi, Chiara; Wistuba, Michael P.
Abstract : This paper presents an investigation on the low-temperature properties of asphalt mixture determined with the indirect tensile (IDT) and the semi-circular bending (SCB) experimental methods. First, IDT and notched and unnotched SCB tests are performed on a set of ten different asphalt mixtures. Then, the maximum stress (strength) along the crack surface of SCB specimens is estimated using a commercial finite-element software and cohesive zone modelling. Finally, a set of simple linear relations between the numerically determined SCB strength on notched specimens and the nominal strength value experimentally measured on IDT specimens is derived. It is found that the newly proposed relationship can be potentially used to predict the asphalt mixtures' nominal strength of IDT specimens based on SCB notched fracture tests. No good correlation could be found between SCB strength on unnotched specimens and the corresponding IDT measurements at this stage. This is most likely due to the simple FEM approach selected and the different failure mechanisms of the SCB unnotched configuration.